Outreach in Archaeology with Agent-Based Modeling: Part 3 of 3. Issue 2 (22nd May 2019) - Crabtree, Stefani A.; Harris, Kathryn; Davies, Benjamin; Romanowska, Iza
Abstract: A major challenge facing archaeologists is communicating our research to the public. Thankfully, new computational tools have enabled the testing and visualization of complex ideas in an easily packageable format. In this article we illustrate not only how agent-based modeling provides a platform for communicating complex ideas, but also how these game-like computer models can be explored and manipulated by members of the public therefore increasing their engagement in archaeological explanations. We suggest that these new digital tools serve as an excellent aid for education on the importance of archaeological sites and artifacts. To illustrate the above we walk the reader through a step-by-step pipeline of how to run an ABM model as an experiment and how to export it into a form ready to be sent to SHPO and THPO offices in tandem with reports. Ultimately, we hope that this work will help demystify the computational archaeology process and lead to more fluency in using agent-based modeling in research and outreach. Abstract : Uno de los mayores desafíos a los que se enfrentan los arqueólogos es hacer llegar nuestra disciplina al público. Afortunadamente, las nuevas herramientas computacionales nos permiten examinar y visualizar ideas complejas en un formato más accesible. En este artículo demostramos como los modelos basados en agentes pueden ser una plataforma eficaz para la comunicación de ideas complejas, así como accesibles al consumo público gracias a su similitud con los videojuegos. Aquí sugerimos que estas nuevas herramientas digitales pueden ser usadas de forma didáctica para educar en la importancia de los yacimientos y artefactos arqueológicos. De esta manera, se pretende guiar al lector paso a paso para ejecutar un modelo como experimento que le permita exportar a las oficinas del gobierno local (SHPO y THPO) en conjunto con los informes arqueológicos. En última instancia, esperamos que este trabajo pueda ayudar a desmitificar el método de la arqueología computacional y permita su uso más frecuente en la investigación y divulgación arqueológica.